Nawala Mangsa 2.0 – Weather Station with BLE Broadcaster - Mochamad Mizanul Achlaq; Moh Noor Al-Azam; Aris Winaya; Maftuchah Maftuchah (Journal of Telematics and Informatics, 2018)
Nawala Mangsa is a weather station system owned by the Computer Science Faculty of Narotama University. The system has been installed in several locations and is used to monitor the temperature and relative humidity of the site for research purposes. All information from the remote, currently stored in the server online via an internet connection. In this latest version (ver-2.0), Nawala Mangsa had some updates, including the use of Raspberry Pi 3 boards, adding a sensor to measure sunlight illumination (TSL2561), and replacing temperature and humidity sensor with BME280 so it can also measure air pressure. The using of a board that equipped with Bluetooth version 4.1, which is Bluetooth Low Energy (BLE) ready, make this version of this Nawala Mangsa can also broadcast the data that are read by the sensor through BLE, in addition to sent to the server over the TCP/IP network. By this way, so the weather station data can be directly read by the mobile device that equipped with BLE observer.